Characteristics of cured egg yolk cookies subtituted with skim milk powder during storage - Nurliyani Nurliyani; Jamhari Jamhari; Widodo Widodo; Citravia Agustin (Faculty of Animal Science, Universitas Brawijaya, 2022)
Cured egg yolk cookies is one of the processed egg products containing egg yolk which has been curing with salt and sugar. The purpose of this study was to evaluation of physical, chemical, microbiological and sensory quality of cured egg yolk cookies with various levels of skim milk powder substitution during storage at room temperature. This study consisted of the treatment of cured egg yolk substitution with skim milk powder (0; 20; 40%) and storage treatment (0; 3; 6; 9 weeks). Each treatment was replicated three times. The data of cookie quality were statistically analyzed using ANOVA. The results showed that cured egg yolk cookies with various skim milk powder substitution have similar physical and chemical characteristics, but substituted cookies had a lower fat content (p<0.05). There were no changes in the moisture content of cookies during 9 weeks of storage. Skim milk powder substitution could increase the peroxide number, but there was no change in the peroxide number during 3 to 9 weeks of storage. The texture of cured egg yolk cookies with 40% skim milk substitution was harder (p<0.05) than the 20% skim milk substitution, whereas there was no change in the texture value of cured egg yolk cookies before and after being stored for 9 weeks. There was no significant deferences in the sensory quality of cookies between unsubstituted and 40% skim milk powder substitution. In conclusion, skim milk powder substitution did not change the physical, chemical, and sensory characteristics, but could reduce fat content, increase the peroxide number and the hardness of cookies. During 9 weeks of storage, cured egg yolk cookies are still acceptable microbiologically.